Role of hybrid reinforcement of carbon nanotubes and graphene nanoplatelets on the electrical conductivity of plasma sprayed alumina coating. Issue 4 (March 2018) - Islam, Aminul; Mukherjee, Biswajyoti; Sribalaji, M.; Rahman, O.S. Asiq; Arunkumar, P.; Babu, K. Suresh; Keshri, Anup Kumar
Abstract: This article reports the effect of hybrid reinforcement of carbon nanotubes (CNTs) (1 wt%) and graphene nanoplatelets (GNPs) (0.5 wt%) on electrical conductivity of atmospheric plasma sprayed alumina (Al2 O3 ) coating. The uniform dispersion of CNTs and GNPs were observed over Al2 O3 matrix. Scratch test revealed the improved inter-splat bonding strength with addition of CNTs and GNPs, which could lead to improved electrical conductivity of Al2 O3 coating. The electrical conductivity increased from ~5 × 10 –12 to ~0.7 S/m, by the addition of CNTs (1 wt%) and GNPs (0.5 wt%) in Al2 O3 coating. A drastic improvement of ~ 12 orders of magnitude in electrical conductivity was observed in Al2 O3 − 1 wt% CNT- 0.5 wt% GNP coatings. This improvement in electrical conductivity was majorly attributed to the lower porosity and strong inter-splat bonding. In addition, availability of more numbers of conductive channels as a result of homogeneous distribution of CNTs/GNPs and clean interface with Al2 O3 has played the significant role in enhancement of electrical conductivity.